Maternal Behavior, Posture Change, and Production Performance of Lactating Sows Housed in an Enriched Environment. Issue 3 (3rd July 2019) - Yi, Ran; Wang, Chao; Zhang, Xin; Zhao, Peng; Zhang, Mingyue; Li, Xiang; Cui, Shiquan; Liu, Honggui; Bao, Jun
ABSTRACT: This study aimed to evaluate whether adding straw to a loose-farrowing house promotes maternal functions and production. Forty-eight sows (Landrace× Large White) were housed in either a farrowing pen without straw (C,  n = 24) or with straw (S,  n = 24). Behaviors were observed using video recordings and were statistically analyzed. Lateral recumbency was higher and standing was lower in S compared with C (p = .034 and p = .020, respectively), and lateral recumbency to other postures, ventral to lateral recumbency and standing to lying were markedly lower in S than C (p = .014, p = .025 and p = .023, respectively) on Day 1 postpartum. However, except piglet losses during the first three days postpartum (p = .032), piglet weight on Day 21 (p = .037), and piglet weaning weight (p = .020), other production performances were not significantly different between the two groups during the whole experimental period (p ˃.05). The results suggest the enrichment of a farrowing pen with straw has important beneficial effects on sow and piglet welfare and improves piglet survival rates.